PENGARUH PEMBERIAN SARI TOMAT (Solanum lycopersicum L) DAN INSULIN TERHADAP KADAR GLUKOSA, KADAR LDL, KADAR KOLESTEROL DAN BERAT BADAN LAHIR TIKUS PUTIH STRAIN WISTAR (Rattus Norvegicus) BUNTING DENGAN MODEL DIABETES MELLITUS TIPE 2 - Savitri, Faradea Ubaidurrohmah; Safitri, Risma Andani Ayu; Maharani, Wening Pangesthi; Andriani, Lela Dwi; Kalsum, Umi; Proborini, Astri; Reksohusodo, Subandi; Dian Hanifarizani, Rahma (Journal of Issues in Midwifery)
Diabetes Mellitus is a chronic disease caused by abnormal working insulin, insulin secretion or both so that the body tends to have high glucose levels. Type 2 diabetes mellitus can cause elevated levels of LDL and cholesterol. Risks obtained by fetuses with type 2 diabetes can be in the form of macrosomia due to hyperglycemia and hyperinsulin in the body of the fetus. Insulin is the first choice pharmacological therapy for type 2 DM that can be given during pregnancy. Non-pharmacological therapy as recommended by the World Health Organization (WHO) on a healthy diet by increasing consumption of fruits and vegetables. Good fruit consumed for pregnant women with diabetes mellitus (DM) type 2 is tomatoes (Solanum lycopersicum L). The purpose of this study was to determine the administration of tomato extract (Solanum lycopersicum L) and insulin can affect glucose levels, LDL levels, cholesterol levels and birth weight of white wistar strain (Rattus norvegicus) pregnant women with type 2 diabetes mellitus models. experimental design using the pre post test only control group design and post test only control group design. Termination was done on the 17th day of pregnancy and then followed by measurements of LDL levels, cholesterol and birth weight. Data analysis using the One Way Anova test and Kruskal Wallis then continued with the Post Hoc test using. The results showed that there were significant differences between glucose levels, LDL levels, cholesterol levels and BW born in the insulin treatment group and the tomato juice treatment (p value = 0.00 <Î± = 0.05). The conclusion of giving insulin and tomato juice affects a decrease in glucose levels, LDL levels, cholesterol levels and birth weight.